Pemiskinan Koruptor Sebagai Alternatif Pidana Tambahan dalam Pemberantasan Tindak Pidana Korupsi di Indonesia Dikaitkan dengan Rancangan Undang-Undangan Perampasan Aset - Jenny Susmita Susilo; Elwi Danil; Nani Mulyati (UNES Law Review, 2023)
In the latest research by Transparency International (TI) in 2022, Indonesia scores 34 out of a total of 100 and is ranked 110 out of 180 countries surveyed. This shows that responses to corrupt practices tend to be slow and even continue to get worse due to the lack of support from stakeholders. Efforts to formulate impoverishment crimes are one of the efforts in reforming criminal law in Indonesia. Impoverishment sanctions for corruptors are considered to be more effective in providing a deterrent effect than prison sentences. The formulation of the problem, namely: 1) What is the setting for impoverishment crimes against perpetrators of corruption as an alternative punishment for corruption 2) What are the obstacles faced in accepting impoverishment punishment as an additional punishment 3) How can the Asset Confiscation Bill accommodate the eradication of criminal acts of corruption in Indonesia. Normative juridical research approach. The research is descriptive analysis in nature, primary and secondary data sources, namely primary, secondary and tertiary legal materials, data were collected by means of library research. Data were analyzed qualitatively. The conclusion of the research results: The regulation of the crime of impoverishment against corruptors as an alternative punishment for corruption in Indonesia has not been regulated explicitly in the laws and regulations for eradicating corruption, where public prosecutors can confiscate and auction off corruptors' property originating from corruption as a substitute for losses of state money. At UNCAC 2003, confiscation of the assets of perpetrators of corruption can be carried out through criminal and civil channels. The criminal provisions contained in the Corruption Crime Eradication Law (UUPTPK) are considered unable to recover state financial losses, this is because, first, court decisions are not proportional to losses. Ideally, the calculation of state financial losses uses the concept of economic costs. The asset confiscation bill has a breakthrough needed by law enforcers to strengthen the legal system whereby asset confiscation is a crime without a court decision in criminal cases (non-conviction-based forfeiture). Through the Asset Confiscation Bill which has been initiated by the government, it is hoped that efforts to recover assets resulting from crime can be streamlined.